Acute perioperative-stress-induced increase of atherosclerotic plaque volume and vulnerability to rupture in apolipoprotein-E-deficient mice is amenable to statin treatment and IL-6 inhibition - Henrike Janssen; Christian S. Wagner; Philipp Demmer; Simone Callies; Gesine Sölter; Houra Loghmani-khouzani; Niandan Hu; Harald Schuett; Uwe J. F. Tietge; Gregor Warnecke; Jan Larmann; Gregor Theilmeier (The Company of Biologists, 2015)
Myocardial infarction and stroke are frequent after surgical procedures and consume a considerable amount of benefit of surgical therapy. Perioperative stress, induced by surgery, is composed of hemodynamic and inflammatory reactions. The effects of perioperative stress on atherosclerotic plaques are ill-defined. Murine models to investigate the influence of perioperative stress on plaque stability and rupture are not available. We developed a model to investigate the influence of perioperative stress on plaque growth and stability by exposing apolipoprotein-E-deficient mice, fed a high cholesterol diet for 7 weeks, to a double hit consisting of 30 min of laparotomy combined with a substantial blood loss (approximately 20% of total blood volume; 400 µl). The innominate artery was harvested 72 h after the intervention. Control groups were sham and baseline controls. Interleukin-6 (IL-6) and serum amyloid A (SAA) plasma levels were determined. Plaque load, vascular smooth muscle cell (VSMC) and macrophage content were quantified. Plaque stability was assessed using the Stary score and frequency of signs of plaque rupture were assessed. High-dose atorvastatin (80 mg/kg body weight/day) was administered for 6 days starting 3 days prior to the double hit. A single dose of an IL-6-neutralizing antibody or the fusion protein gp130-Fc selectively targeting IL-6 trans-signaling was subcutaneously injected. IL-6 plasma levels increased, peaking at 6 h after the intervention. SAA levels peaked at 24 h (n=4, P<0.01). Plaque volume increased significantly with the double hit compared to sham (n=8, P<0.01). More plaques were scored as complex or bearing signs of rupture after the double hit compared to sham (n=5-8, P<0.05). Relative VSMC and macrophage content remained unchanged. IL-6-inhibition or atorvastatin, but not blocking of IL-6 trans-signaling, significantly decreased plaque volume and complexity (n=8, P<0.01). Using this model, researchers will be able to further investigate the pathophysiology of perioperative plaque stability, which can result in myocardial infarction, and, additionally, to test potential protective strategies.